Legal Protection Of Intellectual Property Rights Of Aren Bone Sugar In The Perspective Of Geographic Indications - Jumardi Ardi; Hasbir Paserangi; Marwah (Jurusan Ilmu Hukum Fakultas Syariah dan Hukum uin alauddin, 2022)
This study aims to analyze and identify the characteristics of Bone Palm Sugar so that it has the potential to be registered with geographical indications and identify local government efforts to report Bone Palm Sugar's geographical indications. The research was conducted using empirical research methods by conducting interviews with sources and collecting primary data on palm sugar farmers and district and provincial governments.The description in this study, namely: Bone Palm Sugar has the potential to be registered with geographical indications because it has a distinctive taste characteristic and a sweet palm sugar aroma, the color of the palm sugar produced is chocolate and natural production, the resulting Palm Sugar has the shape uniform, i.e., dry smooth. Geographical conditions Palm sugar, whose processed ingredients are taken from palm/inru/inau trees that grow in several sub-districts spread across Bone regency it is more widely used by the community for tuak drinks (sweet and sour) compared to trees in the highlands or mountains because the sap is suitable for processing palm sugar, and this is mainly produced by people in mountainous areas in Bone Regency. Local government efforts to register geographical indications of sugar Bone sugar palm is not optimal because the Regional Government has understood the importance of registering geographical indications and legally protecting a regional product as evidenced by the application for registration of communal intellectual property. However, the focus is only on cultural matters, even though a palm sugar industry can be developed and registered geographical indications.